2015
DOI: 10.1111/andr.12085
|View full text |Cite|
|
Sign up to set email alerts
|

Restoration of erectile function with intracavernous injections of endothelial progenitor cells after bilateral cavernous nerve injury in rats

Abstract: SUMMARYEndothelial progenitor cells (EPCs) are bone marrow-derived endothelial cells capable of circulating, proliferating, and differentiating into mature endothelial cells. Circulating EPCs can be directly recruited to some extent at sites of injury, and their administration could accelerate repair or endothelialization of the damaged tissue. We investigated the effects of intracavernous injections of EPCs into the corpora cavernosa of rats with erectile dysfunction (ED) caused by bilateral cavernous nerve (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…We have also previously reported that EPC treatment restored EF in a rat model of bilateral CN injury through recruitment of EPCs toward the dorsal artery and preservation of corporal SMCs. These findings support the therapeutic potential of progenitor cells for treating ED in humans [14]. SPCs can limit plaque development and promote changes in plaque composition toward a stable phenotype in mice [15].…”
Section: Introductionsupporting
confidence: 62%
“…We have also previously reported that EPC treatment restored EF in a rat model of bilateral CN injury through recruitment of EPCs toward the dorsal artery and preservation of corporal SMCs. These findings support the therapeutic potential of progenitor cells for treating ED in humans [14]. SPCs can limit plaque development and promote changes in plaque composition toward a stable phenotype in mice [15].…”
Section: Introductionsupporting
confidence: 62%
“…Regarding treatment strategies, a recent study showed that intracavernous injection of EPCs into the corpora cavernosa of rats with erectile dysfunction caused by bilateral cavernous nerve injury could restore erectile function [227]. In summary, the close correlation between erectile dysfunction and penile vascular dysfunction suggests that EPCs may have great therapeutic potential.…”
Section: Current Prospectsmentioning
confidence: 99%
“…Penile erectile function was assessed using ICP and MAP tests as previously reported (Liao et al ., ). The CNs were exposed and a bipolar, stainless steel electrode was used for nerve stimulation.…”
Section: Meterials and Methodsmentioning
confidence: 97%
“…Radical prostatectomy (RP) is the primary treatment for patients with localized prostate cancer. However, the incidence rate of erectile dysfunction (ED) post‐operation remains as high as 30–87% (Liao et al ., ). Currently, the pathophysiology of RP‐ED has not been well‐elucidated (Weyne et al ., ).…”
Section: Introductionmentioning
confidence: 97%